Exercise defined and quantified according to the Systéme International d'Units - Winter, E. M.; Fowler, N. (Journal of Sports Sciences, 2009)
Sport and exercise scientists have a common focus: the scientific study of factors that influence our ability to perform exercise or physical activity. As a result, this ability is assessed and hence quantified. Accordingly, definitions of exercise and related terms and nomenclature that describe the performance of exercise must adhere to principles of science and satisfy the Systme International d'Units (SI) that was adopted universally in 1960. Frequently, these requirements are not met. The aims of this review are twofold: (1) to identify instances of non-compliance and (2) propose universal definitions of exercise and related terms and nomenclature that do conform to the SI and apply to exercise and physical activity that encompasses elite-standard competitive sport, activities of daily living, and clinical applications in rehabilitation and public health. A definition of exercise is offered: a potential disruption to homeostasis by muscle activity that is either exclusively, or in combination, concentric, eccentric or isometric.